IMPLEMENTASI PROYEK ADVOCATING FOR CHANGE (AFC) DALAM MEMPROMOSIKAN HAK PENYANDANG DISABILITAS DI INDONESIA - Relita Hayatun Nugraha; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Disability is still a big issue in developing countries, including Indonesia. They are a part of under-privileged marginal group in the national development process. The low rate of people with disability’s participation in the development process violates their rights. Various policies and programs have been conducted by Indonesian government, yet, not all have been in favor to the rights of people with disability. Humanity and Inclusion (HI) exists in Indonesia to protect the rights of people with disability. One of the projects that HI implemented to increase the participation of people with disability in national development project is the Advocating for Change (AfC) project.  The research method used within this research was qualitative-descriptive. The data was collected from journals, books, official reports, and websites to analyze this research. The perspective used within the research was pluralism perspective and using international organization theory.  The research shows that the implementation of AfC project in promoting the rights for people with disabilities runs well by conducting a set of advocacy activities. The implementation of AfC project shows positive impact, both physically and non-physically.   Keywords : Advocating for Change (AfC), Humanity and Inclusion (HI),  Human Rights, People with Disability, Disabled People Organization (DPO)